'Ala' al-Dawla al-Simnani between spiritual authority and political power a persian lord and intellectual in the heart of the Ilkhanate : with a critical edition and translation of "al-Warid alsarid al-tarid subhat al-marid" and a critical edition of its persian version "Zayn al-mu'taqad li-zayn al-mu'taqid" - Martini, Giovanni Maria (Leiden Boston Brill, 2018)
Giovanni Maria Martini investigates the personality of a major figure in the socio-political and cultural landscape of Mongol Iran. In pursuing this objective, the author follows parallel paths: Chapter I provides the most updated reconstruction of Simnani?s (d. 736/1336) biography, which, thanks to its unique features, emerges as a cross-section of Iranian Society and as a microhistory of the complex relationships between a Sufi master, Persian Elites and Mongol rulers during the Ilkhanid period; Chapter II contains a study on the phenomenon of Arabic-Persian diglossia in Simnani?s written work, arguing for its socio-religious function; in Chapters III to VI the critical editions of two important, interrelated treatises by Simnani are presented; finally, Chapter VII offers the first full-length annotated translation of a long work by Simnani ever to appear in a Western language
Introduction: enhanced and expanded version of PhD dissertation
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Simnānī, Aḥmad ibn Muḥammad -- 1261-1336 -- Criticism and interpretation; Sufis -- Iran -- Biography; Sufism -- Early works to 1800; Hochschulschrift